Advances in Engineering Education in Chile Using Student Feedback - Letelier-Sotomayor, M (Elsevier Ltd., 2012)
Two main social forces are causing universities in Chile increase their effectiveness in translating market and political signals into actions in order to improve the quality and impact of the engineering education they provide. Since 2000 these forces have been expressed in government policies of programme accreditation and funding. This national context is exemplified through the experience at the University of Santiago of Chile. The expectations of the workplace with regard to the strengths and weaknesses of engineering education have been usually expressed through the desired learning outcomes of the programmes, many of which address attitudes rather than scientific or technological aspects. From this perspective, the actual developments in student feedback, considered as a significant resource for quality improvement, are discussed. Finally, some conclusions about structural factors that, in both the industrial sector and the universities, strengthen the achievement of the necessary consistency between the country s needs and university responses are drawn. © 2012 Woodhead Publishing Limited. All rights reserved.